Answer:
<h3>The best interpretation of this equation 4x=3x is that the equation has no solution</h3>
Step-by-step explanation:
Given that Kate begins solving the equation
![\frac{2}{3}(6x-3)=\frac{1}{2}(6x-4)](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D%286x-3%29%3D%5Cfrac%7B1%7D%7B2%7D%286x-4%29)
<h3>To find the best interpretation of the given equation :</h3><h3>Katie's steps are</h3>
When she adds 2 to both sides, the equation becomes
Therefore ![4\neq 3](https://tex.z-dn.net/?f=4%5Cneq%203)
<h3>Therefore the given equation has no solution </h3><h3>The best interpretation of this equation 4x=3x is that the equation has no solution.</h3><h3>Therefore the option no solution is correct</h3>
Answer:
C the coordinates are just fliped since It was flipped on the y- axis
Step-by-step explanation:
Answer:
Step-by-step explanation:
Answer:
12.6 hp
Step-by-step explanation:
Represent the input by n. 10.75 hp
Then 0.85n = 10.75 hp, and n (the input) is --------------- = 12.6 hp
0.85
Answer:
Decreases
Step-by-step explanation:
We need to determine the integral of the DE;
![dP/dt=P(aP-b)](https://tex.z-dn.net/?f=dP%2Fdt%3DP%28aP-b%29)
![dP=P(aP-b)dt](https://tex.z-dn.net/?f=dP%3DP%28aP-b%29dt)
![1/(dP^2-bP)dP=dt](https://tex.z-dn.net/?f=1%2F%28dP%5E2-bP%29dP%3Ddt)
We can solve this by integration by parts on the left side. We expand the fraction 1/P²:
![1/(d-b/P)\cdot{P^2} dP](https://tex.z-dn.net/?f=1%2F%28d-b%2FP%29%5Ccdot%7BP%5E2%7D%20dP)
let
![u=d-b/P](https://tex.z-dn.net/?f=u%3Dd-b%2FP)
![du/dP=b/P^2](https://tex.z-dn.net/?f=du%2FdP%3Db%2FP%5E2)
![dP=](https://tex.z-dn.net/?f=dP%3D)
![\int\limits {P^2/b} \, du](https://tex.z-dn.net/?f=%5Cint%5Climits%20%7BP%5E2%2Fb%7D%20%5C%2C%20du)
![P=lnu/b](https://tex.z-dn.net/?f=P%3Dlnu%2Fb)
Substitute u in:
![P=ln(d-b/P)/b](https://tex.z-dn.net/?f=P%3Dln%28d-b%2FP%29%2Fb)
Therefore the equation is:
![ln(d-b/P)/b=t](https://tex.z-dn.net/?f=ln%28d-b%2FP%29%2Fb%3Dt)
We simplify:
![d-b/P=e^b^t](https://tex.z-dn.net/?f=d-b%2FP%3De%5Eb%5Et)
![P=b/(d-e^b^t)](https://tex.z-dn.net/?f=P%3Db%2F%28d-e%5Eb%5Et%29)
As t increases to infinity P will decrease